Geospatial database use for land consolidation objectives in Ukraine - Malashevskyi, M.; Tarnopolsky, A.; Malashevska, O. (Land Management, Cadastre and Land Monitoring, 2021)
The issue of geospatial database provisioning for land consolidation objectives in Ukraine has been scrutinized in the article. The thematic justification is predefined by the increasing need for land consolidation and the need for the provision of the land consolidation process with the updated, full and valid data. The goal of the research is the substantiation of a set of the subject geospatial data as a constituent of the national infrastructure needed for managerial decisions on agricultural land consolidation and the respective land management plan development. Basic geospatial data sets predefined by the legislation in effect have been examined from the prospect of land consolidation. Thematic geospatial data sets have been suggested.The use of the suggested geospatial data sets in the course of the key stages of land consolidation has been analysed. The use of geospatial data at the implementation of a land consolidation project using the land reallotment optimization model has been examined. The research results can be used at the land consolidation decision making support, land resources management, development of specialized geoportals, in the following scientific researches on the development of the national geospatial data infrastructure, land consolidation in Ukraine.Key words: geospatial data, land consolidation, agricultural land, agricultural land market, land reform.